Natural Variation in the Flag Leaf Morphology of Rice Due to a Mutation of the NARROW LEAF 1 Gene in Oryza sativa L. Issue 2 (13th August 2015) - Taguchi-Shiobara, Fumio; Ota, Tatsuya; Ebana, Kaworu; Ookawa, Taiichiro; Yamasaki, Masanori; Tanabata, Takanari; Yamanouchi, Utako; Wu, Jianzhong; Ono, Nozomi; Nonoue, Yasunori; Nagata, Kazufumi; Fukuoka, Shuichi; et al.
Abstract: We investigated the natural variations in the flag leaf morphology of rice. We conducted a principal component analysis based on nine flag leaf morphology traits using 103 accessions from the National Institute of Agrobiological Sciences Core Collection. The first component explained 39% of total variance, and the variable with highest loading was the width of the flag leaf (WFL). A genome-wide association analysis of 102 diverse Japanese accessions revealed that marker RM6992 on chromosome 4 was highly associated with WFL. In analyses of progenies derived from a cross between Takanari and Akenohoshi, the most significant quantitative trait locus (QTL) for WFL was in a 10.3-kb region containing the NARROW LEAF 1 ( NAL1 ) gene, located 0.4 Mb downstream of RM6992. Analyses of chromosomal segment substitution lines indicated that a mutation (G1509A single-nucleotide mutation, causing an R233H amino acid substitution in NAL1) was present at the QTL. This explained 13 and 20% of total variability in WFL and the distance between small vascular bundles, respectively. The mutation apparently occurred during rice domestication and spread into japonica, tropical japonica, and indica subgroups. Notably, one accession, Phulba, had a NAL1 allele encoding only the N-terminal, or one-fourth, of the wild-type peptide. Given that the Phulba allele and the histidine-type allele showed essentially the same phenotype, the histidine-type allele was regarded as malfunctional. The phenotypes of transgenic plants varied depending on the ratio of histidine-type alleles to arginine-type alleles, raising the possibility that H 233 -type products function differently from and compete with R 233 -type products.